Design of Automatic Scoring Device for Soccer Goal Based on Computer Vision - Qiao, Dan; Du, Gang; Zhang, Wenhui; Dai, Yumeng (2020 International Conference on Computer Information and Big Data Applications (CIBDA), 2020)
Football is one of the most fashionable games in the world, meanwhile the refereeing results may be controversial. In this work, an automatic goal scoring system is designed for the specific games based on computer vision. The aim is to simplify the referee's work, reduce the human error, and provide an accurate performance for the operators. This subject can realize the tracking and identification of football as the movement of the entity, the detection of the ball into the goal of the scoring area. Through the actual test, the design can accurately display the score results.